EVALUASI PROBIOTIK KOMERSIAL YANG BERBEDA TERHADAP EFISIENSI PAKAN DAN SINTASAN BENIH IKAN PATIN SIAM (Pangasius hypophthalmus) - Dedek Mariadi; Fazril Saputra; Mahendra Mahendra; Dini Islama; Yusran Ibrahim; Radhi Fadhillah; Muhammad Arif Nasution; Muhammad Agam Thahir (Universitas Teuku Umar, 2022)
Siamese pangasius fish (Pangasius hypophthalmus) is a freshwater fish species originated from species introduced and has economic value for cultivation. This study aimed to analysed the administration of different commercial probiotics through feed on the survival rate and feed efficiency of Siamese pangasius fish. This research was conducted in the hatchery of Teuku Umar University. The method used a completely randomized design with 4 treatments and 3 replications. The treatments were control/administration of Mina Pro (P0) commercial probiotic, administration of Raja Grameh (P1) commercial probiotic, administration of EM4 (P2) commercial probiotic and administration of Boster (P3) commercial probiotic. Parameters observed were survival, feed efficiency, and water quality. Data were analysed using analysis of variance; for different treatments, Duncan's test was carried out. The results showed that the administration of different commercial probiotics had a significant (P<0.05) effect on feed efficiency but had no significant effect (P>0.005) on the survival rate of Siamese pangasius fish. Raja Grameh's commercial probiotic with the composition of Rhodobacter sp., Lactobacillus sp., Acetobacter sp., and yeast were the best commercial probiotic to increase the growth and feed efficiency of Siamese pangasius fish